COVID-19 Vaccine Hesitancy Associated With Vaccine Inequity Among Healthcare Workers in a Low-Income Fragile Nation - Noushad, Mohammed; Nassani, Mohammad Zakaria; Al-Awar, Mohammed Sadeg; Al-Saqqaf, Inas Shakeeb; Mohammed, Sami Osman Abuzied; Samran, Abdulaziz; Yaroko, Ali Ango; Barakat, Ali; Elmi, Omar Salad; Alsalhani, Anas B.; Talic, Yousef Fouad; Rastam, Samer (Frontiers in Public Health, 2022)
Objectives Preventing severe disease and acquiring population immunity to COVID-19 requires global immunization coverage through mass vaccination. While high-income countries are battling vaccine hesitancy, low-income and fragile nations are facing the double dilemma of vaccine hesitancy and lack of access to vaccines. There is inadequate information on any correlation between vaccine hesitancy and access to vaccines. Our study in a low-income nation aimed to fill this gap. Methods In the backdrop of a severe shortage of COVID-19 vaccines in Yemen, a low-income fragile nation, we conducted a nation-wide cross-sectional survey among its healthcare workers (HCWs), between 6 July and 10 August 2021. We evaluated factors influencing agreement to accept a COVID-19 vaccine and any potential correlation between vaccine acceptance and lack of access to vaccines. Results Overall, 61.7% (n = 975) of the 1,581 HCWs agreed to accept a COVID-19 vaccine. Only 45.4% of the participants agreed to have access to a COVID-19 vaccine, with no sex dependent variations. Although several determinants of vaccine acceptance were identified, including, having a systemic disease, following the updates about COVID-19 vaccines, complying with preventive guidelines, having greater anxiety about contracting COVID-19, previous infection with COVID-19, believing COVID-19 to be a severe disease, and lower concern about the side effects of COVID-19, the strongest was access to vaccines (OR: 3.18; 95% CI: 2.5–4.03; p-value: 0.001). Conclusion The immediate and more dangerous threat in Yemen toward achieving population immunity is the severe shortage and lack of access to vaccines, rather than vaccine hesitancy, meaning, improving access to vaccines could lead to greater acceptance.